Time-varying linkages of economic activities in China and the stock markets in ASEAN-5 - Kee Tuan Teng; Siew Hwa Yen; Soo Y. Chua; Hooi Hooi Lean (Contemporary Economics, 2016)
This study attempts to investigate the evolution of dynamic linkages and volatility spillover between the five countries of the Association of Southeast Asian Nations (ASEAN-5) stock markets and China's economic activities. By using the movements and structural breaks of the time-varying correlation and Granger causality test, a suitable destination for equity portfolio diversification can be determined among the studied markets. This study covers monthly data from January 1991 to March 2015. The DCC-MGARCH model shows that the studied countries are time-varying correlated, while the structural break observed by Bai and Perron test coincided with major economic shocks, policy changes and the establishment of regional trade policies. The VAR model Granger causality test observed no volatility spillover from Chinese economic activities to the ASEAN-5 stock markets, except for Malaysia and the Philippines. However, the ASEAN-5 stock markets' volatility exerts a significant influence on China's economy, except for Singapore's stock market volatility. This study reveals that ASEAN-5 has gradually became the preferred destination for diversifying equity portfolios for investors in China.
Keywords: F15; F36; 330; ASEAN; China; financial integration; volatility spillover